Gerador termoelétrico de exaustão automotiva com permutador de calor de aletas e minicanais corrugados - Barbosa Junior, Cleiton Rubens Formiga (2024)
The present thesis focuses primarily on the research of development and transient analysis of the performance of a prototype of an automotive exhaust thermoelectric generator (TEGea) for recovering energy from the exhaust gases of an automotive thermal engine. The numerical modeling and simulation of the TEGea prototype were based on empirical data input into ANSYS, assisting in defining the configuration of high and low-temperature heat exchangers and pre-selecting thermoelectric modules, as well as predicting exhaust temperature profiles in the TEGea section and estimating thermoelectric conversion performance. The proposed material for the TEGea heat exchangers was aluminum due to its high thermal conductivity, low density, and easy machinability. The design of the hightemperature heat exchanger features a rectangular geometry and internal fins with corrugated minicanals to enhance heat capture and transfer from hot gases to thermoelectric modules. The low-temperature heat exchanger also has a rectangular geometry and an internal channel for coolant flow to maximize thermal exchanges and reduce pumping losses. An instrumented test bench (hot air tunnel) was developed for transient analysis of the TEGea prototype performance. The results obtained show that the insertion of internal fins with corrugated minicanals in the heat exchanger of the hot source intensifies heat capture, contributing to the higher efficiency of the proposed TEGea.